EDITORIAL (American Journal of Islam and Society, 1992)
We are pleased to present the first summer issue of our new quarterlyschedule. This will, in sha' Allah, be followed by our fall issue in September1992 and winter issue in December 1992.In this issue, Mahmoud Dhaouadi discusses the nature of human culturalsymbols such as language, thought, religious beliefs, knowledge, cultural normsand values, and science. The essay develops a basic theoretical framework forstudying the nature of what he describes as a cultural-symbolic soul. It thenproceeds to apply this new concept to understandmg as well as devising a potentialexplanation of the dynamics of cultural-symbolic exchange and confrontationbetween human groups regardless of time and space constraints. Dhaouadiattempts to provide a balanced contribution to the ever-growing body ofknowledge in the modem social and behavioral sciences by trying to work outa synthesis between theory and application, which, if executed successfully,would enhance the scientific credibility of the behavioral and social sciences.Dhaouadi pleads that by paying attention to other epistemologies, ideas,concepts, theories, and methodologies, an initial step could be taken towardsresolving the crisis which the social sciences have been experiencing in the Westsince the 1970s. He believes that the continuing growth of the body of knowledgein the Islamic behavioral and social sciences will equip its practitioners withthe knowledge to make constructive contributions to the reform of Westernbehavioral and social scientific thought.Muhammad Y. Faruqi traces the development of ijma' from the practiceof the Companions of the Prophet to the classical fuqaha' . The jurists of thefour established schools of fiqh consider ijma', a concept which evolved as alegal doctrine during the second hijri century, as the third source after the Qur'anand the Sunnah.Farqui discusses the kinds of ijma' and raises the issue of the infallibilityof ijma' . He argues that if the views of the classical jurists were adopted, ineffect no one would be allowed to disagree or have a different opinion, as thiswould jeopardize the ummah's infallibility. He supports Ibn Hazm's view thatconsensus must be based on a nass from either the Qur'an, the hadith, or both.As these sources are infallible, any resulting consensus will also be infallible.He brings up the interpretation of al Juwayni, who states that there is noclear Qur'anic or hadith text referring to the principle of ijma'. Al Juwayni provesthe authority of consensus by arguing that there are certain issues related to haram ...